EVALUASI KEMAMPUAN KOGNITIF SISWA TERHADAP HASIL BELAJAR IPS KELAS IV SD NEGERI 27 BANYUASIN III - Elsa Pulungan (JS (JURNAL SEKOLAH), 2022)
Abstract  : Evaluation of Students cognitive abilities on social studie learning outcomes for grade IV SD Negeri 27 Banyuasin III. Learning evaluation is a process of activities in order to determine the process and learning outcomes of students as a form of determining the success of teachers in carrying out learning activities. This study aims to analyze and describe students' cognitive abilities towards social studies learning outcomes for grade IV SD Negeri 27 Banyuasin III. The research method used is descriptive research method with a quantitative approach. The technique used to collect data is a questionnaire (questionnaire), interviews, and documentation. Data analysis using descriptive statistics by using the mean, median, mode, and standard deviation with group data. In conclusion, it can be concluded that students' cognitive abilities towards social studies learning outcomes for grade IV at SD Negeri 27 Banyuasin III are quite good, we can see from the results of the overall questionnaire recapitulation with the percentage of results quite good at 43.61% with the percentage of the assessment scale or dominant answering quite both on a scale of 3 students amounted to 14.71% and based on the results of the recapitulation on students' cognitive abilities, then on each indicator of students' cognitive abilities more dominantly answered on the indicator of ability to evaluate the score of 211 an average of 50.24% with good category, at learning outcomes obtained an average value of 71 with a sufficient category, this is clarified by the results of the fourth grade teacher interviews Keyword : Evaluation, Cognitive Ability, Learning Outcomes Abstak   : Evaluasi kemampuan kognitif siswa terhadap hasil belajr IPS kelas IV SD Negeri 27 Banyuasin III. Evaluasi pembelajaran adalah suatu proses kegiatan dalam rangka untuk menentukan proses dan hasil belajar peserta didik sebagai bentuk menentukan keberhasilan guru dalam melaksanakan kegiatan pembelajaran. Penelitian ini bertujuan untuk menganalisis dan mendeskripsikan kemampuan kognitif siswa terhadap hasil belajar IPS kelas IV SD Negeri 27 Banyuasin III. Metode penelitian yang digunakan adalah metode penelitian deskriptif dengan pendekatan kuantitatif. Teknik yang digunakan untuk mengumpulkan data adalah angket (kuensioner), wawancara, dan dokumentasi. Analisis data dengan menggunakan statistik deskriptif yakni dengan menggunakan mean, median, modus, dan simpangan baku dengan data kelompok. Kesimpulan maka dapat disimpulkan bahwa kemampuan kognitif siswa terhadap hasil belajar IPS kelas IV di SD Negeri 27 Banyuasin III yakni cukup baik dapat kita lihat dari hasil rekapitulasi keseluruhan angket dengaan persentase hasil dengan cukup baik sebesar 43,61% dengan persentase sekala penilaian atau dominan menjawab cukup baik pada sekala 3 siswa sebesar 14,71 % dan berdasarkan hasil rekapitulasi pada kemampuan kognitif siswa, kemudian pada masing – masing indikator kemampuan kognitif siswa lebih dominan menjawab pada indikator kemampuan mengevaluasi skor nilai 211 rata – rata 50,24% dengan kategori baik, pada hasil belajar diperoleh nilai rata-rata sebesar 71 dengan kategori cukup, hal tersebut diperjelas dengan hasil wawancara guru kelas IVKata Kunci  : Evaluasi, Kemampuan Kognitif, Hasil Belajar